Determinants of Tax Avoidance in Manufacturing Companies in Indonesia: Empirical Evidence from Fundamental Financial Factors - Ni Luh Gede Mahayu Dicriyani; I Made Marsa Arsana (PT Keberlanjutan Strategis Indonesia, 2026)
Tax avoidance is a strategic issue in taxation because it has the potential to reduce state revenues, even though it is carried out through mechanisms that are still within the legal corridor. Various studies on the determinants of tax avoidance in manufacturing companies in Indonesia still show inconsistent results, particularly regarding the influence of sales growth, profitability, liquidity, leverage, and company size. T. The study uses a quantitative approach with secondary data obtained from the annual financial reports of manufacturing companies during the study period. The research sample was determined using a purposive sampling technique, resulting in 11 companies with a total of 44 observations. Data analysis was performed using multiple linear regression after all classical assumptions were met. The results show that sales growth, profitability, liquidity, leverage, and company size simultaneously influence tax avoidance. Partially, liquidity has a positive effect on tax avoidance, while leverage has a significant effect, with the direction of the relationship indicating that higher leverage increases the tendency for tax avoidance, as proxied by the Cash Effective Tax Rate (CETR). Meanwhile, sales growth, profitability, and company size do not significantly influence tax avoidance. The findings of this study strengthen empirical evidence that tax avoidance practices are influenced not only by a company's ability to generate profits, but also by the characteristics of its funding structure and liquidity. The research findings are expected to provide input for company management in formulating effective tax strategies and for tax authorities in developing risk-based oversight of corporate taxpayers.